The Big Scrapbook: The relational perspective of Alison Smithson - Casino, David (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
The article explores the creative flexibility that Alison Smithson boasted in combining their design interests is presented through bi-dimensional works on paper that endowed their work with a powerful experimental, visual and artistic dimension. Through the screening of the surprising and thus far unrenowned document called The Big Scrapbook, we perceive the associative and relational sight that this architect deployed towards everything around her, thus constructing a particular imaginary of fragments with which to build new arguments and narratives. Inside this personal atlas of ideas called The Big Scrapbook, the apparently random juxtaposition of a series of images captured from varying times and significances places boosts new connections and creative processes. These novel relationships between pieces of images can be seen as the origin of certain pivotal interests intellectually underpinning the Smithsons’ designs.
Keywords: Alison and Peter Smithson; Scrapbook; Assembly; Fragment; Atlas; Relational